1989
DOI: 10.1037/0012-1649.25.5.780
|View full text |Cite
|
Sign up to set email alerts
|

Aging and memory for action events: The role of familiarity.

Abstract: Two experiments with young and elderly adults explored age-related memory differences for performed action events varying in familiarity. Memory for similar items encoded verbally was also assessed. The findings demonstrated that type of encoding and item-familiarity influenced immediate as well as delayed free recall in both age groups. Highest recall performances were found for familiar performed items. Both factors affected memory performance separately and did not compensate for each other, either in immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 20 publications
6
45
0
Order By: Relevance
“…The observed age differences both in the enacted and nonenacted conditions are consistent with past research (Conway & Dewhurst, 1995;Nilsson & Craik, 1990; see also Cohen et al, 1987;Knopf & Niedhardt, 1989). Significant age effects were found for both item and source recall, with source memory being more age-related than item memory.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The observed age differences both in the enacted and nonenacted conditions are consistent with past research (Conway & Dewhurst, 1995;Nilsson & Craik, 1990; see also Cohen et al, 1987;Knopf & Niedhardt, 1989). Significant age effects were found for both item and source recall, with source memory being more age-related than item memory.…”
supporting
confidence: 89%
“…It is well documented that enacted tasks produce better memory performance than nonenacted tasks (Bfickman & Nilsson, 1984Cohen, 1981Cohen, , 1983Engelkamp & Zimmer, 1984Kormi-Nouri, 1995;Kormi-Nouri, Nilsson, & B~ickman, 1994). Past aging research on the role of enactment in episodic memory tasks has revealed mixed results, with some studies showing no differences between young and older participants in memory for performed actions (Bfickman & Nilsson, 1984, others showing small age differences (Nyberg, Nilsson, & B~ickman, 1992), and still others showing large differences (Cohen, Sandler, & Schroeder, 1987;Knopf & Niedhardt, 1989;Nilsson & Craik, 1990). Thus, one of the objectives of this study was to further clarify the relation between age and action memory.…”
Section: Introductionmentioning
confidence: 93%
“…Both Nilsson, Cohen and Nyberg (1989) and Knopf and Neidhardt (1989) note that SPT effects only last in the short term, after which enhanced SPT or verbal learning attrition progresses at the same rate. Ellis (1995) considers that for effective productive vocabulary learning, the keyword technique must be complemented with repetition practice.…”
Section: The Importance Of Repetitionmentioning
confidence: 99%
“…The term “subject-performed task” (SPT), as opposed to “verbal task” (VT), is used to refer to the tasks exploring this effect. Numerous studies have already evidenced the enactment effect through different experimental protocols with young participants, regardless of the retention interval [3], the familiarity of actions [4], or the use of real or imagined objects [5], thereby underlining its robustness. In addition, it is also described as a robust effect in ageing [6, 7].…”
Section: Introductionmentioning
confidence: 99%